Recent Advances in Tomato Breeding and Production - Tatu Nyaku, Seloame; Danquah, Agyemang (IntechOpen, 2019)
Tomato cultivation is a major economic activity in many countries of the world. Thus, strategic efforts should be directed towards mitigating production constraints that limit overall yields and quality. In addressing some of these constraints, researchers are developing and using varieties of modern and innovative techniques to improve local tomato germplasm, make rapid genetic gains, and breed for varieties with resistance to biotic and abiotic stress. This book focuses on recent advances in genomics and genetic improvement of the tomato crop, and production systems, and center around the following themes: (i) disease and pest management in tomato production, and (ii) breeding tools and improvement of the tomato.